Vocational Counseling and Training for Medical Degrees - Belkis Mercedes Vicente Sánchez; Ernesto Vicente Pena; Mabel Rocha Vázquez; Miriam Costa Cruz (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2014)
Deciding on a university degree is undoubtedly a difficult choice. This situation brings about fear of failing and disappointing yourself and others, which is a common feeling among high school students, becoming a source of anxiety and stress. This demonstrates the need for an appropriate vocational and professional guidance. In Cuba, this subject is gaining importance, since a greater number of youngsters have the opportunity to choose from more professions; thus, deciding on one or the other is a problem of great practical and social impact. Vocational guidance and training in the Cuban educational context aims to reaffirm the inclination of youth towards medical studies, where they fully develop their potential, on the basis of consolidating values and feelings, and a high social, moral and unconditional commitment to the practice of the profession. This paper presents various issues that currently affect vocational guidance and the role of each of the major participants in the process itself.